2021
DOI: 10.3389/fcell.2020.608530
|View full text |Cite
|
Sign up to set email alerts
|

Microclusters as T Cell Signaling Hubs: Structure, Kinetics, and Regulation

Abstract: When T cell receptors (TCRs) engage with stimulatory ligands, one of the first microscopically visible events is the formation of microclusters at the site of T cell activation. Since the discovery of these structures almost 20 years ago, they have been studied extensively in live cells using confocal and total internal reflection fluorescence (TIRF) microscopy. However, due to limits in image resolution and acquisition speed, the spatial relationships of signaling components within microclusters, the kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…7 ; Su et al, 2016 ). Protein phase separation induced by the LAT-GRB2-SOS1 scaffold stabilizes the recruitment of “client” proteins and organizes them into liquid-like condensates (also known as microclusters; Balagopalan et al, 2021 ). They facilitate downstream signaling events such as actin polymerization and activation of the RAS-MAPK-ERK, NFAT, and NF-κB signaling pathways ( Ditlev et al, 2018 ; Ditlev et al, 2019 ; Huang et al, 2017 ; Su et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…7 ; Su et al, 2016 ). Protein phase separation induced by the LAT-GRB2-SOS1 scaffold stabilizes the recruitment of “client” proteins and organizes them into liquid-like condensates (also known as microclusters; Balagopalan et al, 2021 ). They facilitate downstream signaling events such as actin polymerization and activation of the RAS-MAPK-ERK, NFAT, and NF-κB signaling pathways ( Ditlev et al, 2018 ; Ditlev et al, 2019 ; Huang et al, 2017 ; Su et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…TCR-mediated signaling iniBates formaBon of sub-micron sized molecular aggregates called microclusters (MC). These molecular structures, now known to be phase-separated condensates, contain transmembrane receptors, co-receptors, membrane-associated and cytoplasmic kinases, enzymes and adapter proteins 2,4,[26][27][28][29] . Complex phosphorylaBon and dephosphorylaBon events, and the spaBal arrangements and stoichiometry of these molecules regulate signaling from these MCs from the iniBaBon of acBvaBon.…”
Section: Discussionmentioning
confidence: 99%
“…Balagopalan and colleagues have recently shown that upon stimulus, the formation of native TCR nanoclusters in the resting T cell membrane improves signal transduction [ 32 ]. Based on this result, we hypothesized that the distinct qualities of preformed receptor assemblies in the unstimulated CAR T cell’s membrane, as well as the diffusional mobility of the chimeric antigen receptors, could affect the formation of the immunological synapse and early activation signaling events upon engagement with the specific tumor target.…”
Section: Discussionmentioning
confidence: 99%